ON THE QUESTION OF THE LEGAL REGULATION OF DEBT RECOVERY (COLLECTOR ACTIVITY - Zhakupov , Руслан Елюбаевич; Ayapbergenova, Арман Каиргельдиновна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
This article discusses the problematic issues of regulation of debt recovery and the ways of their solutions.